Personal Diexis in "Lebih Senyap dari Bisikan" Novel By Andina Dwifatma - Julisah Izar; Rengki Afria; Neldi Harianto; Maraatun Soliha; Putri Mawaddah Warohmah (Proceeding International Conference on Malay Identity, 2022)
Abstract:This study aims to determine the use of persona diexis as well as the functions and meanings contained in the novel Lebih Senyap dari Bisikan karya Andina Dwifatma.. The method used in this study is a descriptive method with a qualitative research form. Based on the results of the analysis, there were a singular first person, plural first person, singular second person, singular third person, and plural third person. The use of the first singular persona was often used in this novel, because this story was told by my character. Keywords: Pragmatic, Persona Diexis, Novel Keywords: pragmatic, persona, deixis, novel